The Living together is easy. - Osaka, Eriko; Smith, Jason (Mito-shi : Contemporary Art Center Art Tower Mito Mito-shi, 2004)
Hall, Fiona ; Laing, Rosemary ; Motomiya, Kaoru ; Nakamura, Tetsuya ; Namunjdja, Samuel ; Norrie, Susan ; Rosetzky, David ; Shinoda Taro ; Swallow, Ricky ; Tabaimo ; Takamine, Tadasu ; Akira Yamaguchi
Engels
Japans
Exhibition. Living together is easy. Contemporary Art Center Art Tower Mito Mito-shi. 24-1-2004. 28-3-2004
boek